Including adolescents of childbearing potential in clinical trials with possible exposure to teratogenic medication: a challenge for paediatricians and researchers (Swiss Medical Weekly, 2020)
The issue of contraception and pregnancy tests among minor adolescent women participating in clinical trials, whether healthy or suffering from a disease, represents a challenging issue for paediatricians and researchers, given the potential harmful effect of various therapeutic procedures being tested. First, they need to gauge at what age or developmental stage they need to impose pregnancy tests and contraception. Second, if the adolescent denies any sexual activity, it may be ethically questionable to impose such procedures. Third, these professionals must deal with the issue of confidentiality, taking into account the fact that some adolescents engage in penetrative sexual intercourse without their parents or caregivers knowing. Fourth, in such cases, they must assess the extent to which a minor adolescent can be considered as competent (capable of making autonomous decisions) and deserves privacy and confidentiality. There is indeed a legal obligation for the provider to check that sexual experiences and intercourse take place within a safe relationship. Fifth, if the prescription of contraception is warranted, they have to decide who should assist the adolescent in choosing the method. Finally, with the occurrence of a positive pregnancy test, they may face the rare instance of a competent minor adolescent who refuses to inform her parents. This article has been developed by a group of experts under the auspices of swissethics, the Swiss Association of Research Ethics Committees and SwissPedNet, the umbrella organisation that coordinates the paediatric research in Switzerland. The paper reviews how to address practical and ethical questions regarding minor adolescents of childbearing potential enrolled in a clinical trial that may involve teratogenic medication and offers a series of concrete advice and tools for dealing with problematic situations. Most paediatric protocols stipulate that adolescents included in clinical trials involving potentially teratogenic drugs should undergo pregnancy tests and use contraception. The circumstances in which such requirements are undertaken, however, has not been sufficiently addressed. The recommendations presented in this article will assist researchers in assessing which circumstances apply when considering minor adolescents as individuals with childbearing potentials. It also offers concrete suggestions for tackling such situations.